Projective Norms and Convergence of Norm-Attainable Operators - Okelo, N. B.; Ongati, Omolo; Karieko, Obogi Robert (Journal of Global Research in Mathematical Archives, 2014)
Let H be an infinite dimensional complex Hilbert space and B(H) the algebra of all bounded linear operators on H. We establish norm-attainability of operators via projective tensor norm. Moreover, we give results on the convergence of norm-attainable operators.
Keywords: Projective tensor norm; Norm-attainable operators; Conver-gence